![image](https://tex.z-dn.net/?f=10%29OD3%3A%5C%5Cx%5E2-2x%3E0%5C%5Cx%3D0%5C+%3Bx%3D2%5C%5C%5C_%5C_%5C_%2B%5C_%5C_%5C_%280%29%5C_%5C_%5C_-%5C_%5C_%5C_%282%29%5C_%5C_%2B%5C_%5C_%3Ex%5C%5Cx%5Cin%28-%5Cinfty%3B0%29%5Ccup%282%3B%5Cinfty%29%5C%5Clog_3%28x%5E2-2x%29%3E1%5C%5Cx%5E2-2x%3E3%5C%5Cx%5E2-2x-3%3D0%5C%5Cx_1%3D3%5C+%3Bx_2%3D-1%5C%5C%2F%2F%2F%2B%2F%2F%2F%280%29%5C_%5C_%5C_-%5C_%5C_%5C_%282%29%2F%2F%2F%2F%2B%2F%2F%2F%2F%2F%3Ex%5C%5C%2F%2B%2F%28-1%29%5C_%5C_%5C_%5C_%5C_%5C_%5C_-%5C_%5C_%5C_%5C_%5C_%5C_%5C_%5C_%283%29%2F%2F%2B%2F%2F%3Ex%5C%5Cx%5Cin%28-%5Cinfty%3B-1%29%5Ccup%283%3B%2B%5Cinfty%29)
0\\x=0\ ;x=2\\\_\_\_+\_\_\_(0)\_\_\_-\_\_\_(2)\_\_+\_\_>x\\x\in(-\infty;0)\cup(2;\infty)\\log_3(x^2-2x)>1\\x^2-2x>3\\x^2-2x-3=0\\x_1=3\ ;x_2=-1\\///+///(0)\_\_\_-\_\_\_(2)////+/////>x\\/+/(-1)\_\_\_\_\_\_\_-\_\_\_\_\_\_\_\_(3)//+//>x\\x\in(-\infty;-1)\cup(3;+\infty)" alt="10)OD3:\\x^2-2x>0\\x=0\ ;x=2\\\_\_\_+\_\_\_(0)\_\_\_-\_\_\_(2)\_\_+\_\_>x\\x\in(-\infty;0)\cup(2;\infty)\\log_3(x^2-2x)>1\\x^2-2x>3\\x^2-2x-3=0\\x_1=3\ ;x_2=-1\\///+///(0)\_\_\_-\_\_\_(2)////+/////>x\\/+/(-1)\_\_\_\_\_\_\_-\_\_\_\_\_\_\_\_(3)//+//>x\\x\in(-\infty;-1)\cup(3;+\infty)" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=11%29OD3%3A%5C%5C%5Cfrac%7B6-x%7D%7Bx%2B1%7D%3E0%5C%5C6-x%3D0%5C+%3Bx%2B1%3D0%5C%5Cx%3D6%3Bx%3D-1%5C%5C%5C_%5C_-%5C_%5C_%5C_%28-1%29%2F%2F%2F%2B%2F%2F%2F%286%29%5C_%5C_%5C_-%5C_%5C_%3Ex%5C%5Clog_%5Cfrac%7B1%7D%7B2%7D%5Cfrac%7B6-x%7D%7Bx%2B1%7D%5Cleq-2%3B%5Cfrac%7B1%7D%7B2%7D%3C1%5C%5C%5Cfrac%7B6-x%7D%7Bx%2B1%7D%5Cgeq4%5C%5C%5Cfrac%7B6-x%7D%7Bx%2B1%7D-4%5Cgeq0%5C%5C%5Cfrac%7B6-x-4x-4%7D%7Bx%2B1%7D%5Cgeq0%5C%5C%5Cfrac%7B2-5x%7D%7Bx%2B1%7D%5Cgeq0%5C%5C2-5x%3D0%5C+%3Bx%2B1%3D0%5C%5Cx%3D0%2C4%5C+x%3D-1%5C%5C%5C_%5C_-%5C_%5C_%5C_%28-1%29%2F%2F%2F%2B%2F%2F%2F%286%29%5C_%5C_%5C_-%5C_%5C_%3Ex%5C%5C%5C_%5C_-%5C_%5C_%5C_%28-1%29%2F%2B%2F%5B0%2C4%5D%5C_%5C_%5C_-%5C_%5C_%3Ex%5C%5Cx%5Cin%28-1%3B0%2C4%5D)
0\\6-x=0\ ;x+1=0\\x=6;x=-1\\\_\_-\_\_\_(-1)///+///(6)\_\_\_-\_\_>x\\log_\frac{1}{2}\frac{6-x}{x+1}\leq-2;\frac{1}{2}<1\\\frac{6-x}{x+1}\geq4\\\frac{6-x}{x+1}-4\geq0\\\frac{6-x-4x-4}{x+1}\geq0\\\frac{2-5x}{x+1}\geq0\\2-5x=0\ ;x+1=0\\x=0,4\ x=-1\\\_\_-\_\_\_(-1)///+///(6)\_\_\_-\_\_>x\\\_\_-\_\_\_(-1)/+/[0,4]\_\_\_-\_\_>x\\x\in(-1;0,4]" alt="11)OD3:\\\frac{6-x}{x+1}>0\\6-x=0\ ;x+1=0\\x=6;x=-1\\\_\_-\_\_\_(-1)///+///(6)\_\_\_-\_\_>x\\log_\frac{1}{2}\frac{6-x}{x+1}\leq-2;\frac{1}{2}<1\\\frac{6-x}{x+1}\geq4\\\frac{6-x}{x+1}-4\geq0\\\frac{6-x-4x-4}{x+1}\geq0\\\frac{2-5x}{x+1}\geq0\\2-5x=0\ ;x+1=0\\x=0,4\ x=-1\\\_\_-\_\_\_(-1)///+///(6)\_\_\_-\_\_>x\\\_\_-\_\_\_(-1)/+/[0,4]\_\_\_-\_\_>x\\x\in(-1;0,4]" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=12%29OD3%3A%5C%5C3%5Ex-8%3E0%5C%5C3%5Ex%3E8%5C%5Cx%3Elog_38%5C%5Clog_3%283%5Ex-8%29%3D2-x%5C%5C3%5Ex-8%3D3%5E%7B2-x%7D%5C%5C3%5Ex-8%3D%5Cfrac%7B9%7D%7B3%5Ex%7D%7C3%5Ex%5C%5C3%5E%7B2x%7D-8%2A3%5Ex-9%3D0%5C%5C3%5Ex%3D9%5C+3%5Ex%3D-1%5C%5Cx%3D2)
0\\3^x>8\\x>log_38\\log_3(3^x-8)=2-x\\3^x-8=3^{2-x}\\3^x-8=\frac{9}{3^x}|3^x\\3^{2x}-8*3^x-9=0\\3^x=9\ 3^x=-1\\x=2" alt="12)OD3:\\3^x-8>0\\3^x>8\\x>log_38\\log_3(3^x-8)=2-x\\3^x-8=3^{2-x}\\3^x-8=\frac{9}{3^x}|3^x\\3^{2x}-8*3^x-9=0\\3^x=9\ 3^x=-1\\x=2" align="absmiddle" class="latex-formula">
3^x=-1 решения не имеет